Pemikiran Ali Syari’ati dalam Sosiologi (Dari Teologi Menuju Revolusi) - Faiq Tobroni (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2015)
Ali Syari’ati is muslim brilliant philosopher, graduated from doctoral of Sorbonne France. He created social teology perspective, based from his experience in west sociology perspective about Capitalism or Marxism. He succeed seek the Capitalism and Marxism weaknes if this perspective is used in Muslim Society. He mapping structure of society, insist of: Habil and Qobail. Habil is common people in society, Qabil is high class, likes: prince, aristocrats or capital owner. Qabil was repressedHabil trough social, politic, economy and religious system. This tragedy happen in Iran whenSyah Reza rezim. The consequences, Ali Syari’ati propagandist rebellion Habil to Qabil. Because of his activities, he to be prisoner one more time, then he is going abroad, until he pass away in England (with suspicious that he killed by Syah Reza people). The Iran Revolution happen, after 2 years Ali Syaria’ti pass away